Coordination and optimization of grid-tied power converters from pulse width modulation perspective - Gao, Feng; Xu, Tao (Power systems, 2022)
This book investigates the control and optimization of grid-tied power converters, with a special attention attached to pulse width modulation, which determines the size and cost of power converters as well as switching harmonics. Through the methods introduced in this book, multiple grid-tied power converters safely operate and coordinate in a highly efficient and reliable fashion, thereby boosting the operation of modern power grids. To facilitate understanding, the key methods are presented together with their associated algorithms and detailed software codes. In parallel to theoretical treatments, this book further applies the methods into practical scenarios and industrial products, thus enhancing their credibility. The book serves as a guidance for electrical engineers and researchers in the field of power electronics and power systems